2016
DOI: 10.1189/jlb.5a1115-508rr
|View full text |Cite
|
Sign up to set email alerts
|

Gr-1intCD11b+ myeloid-derived suppressor cells accumulate in corneal allograft and improve corneal allograft survival

Abstract: We identified the characteristics of myeloid-derived suppressor cells (MDSCs) and investigated their mechanism of induction and their functional role in allograft rejection using a murine corneal allograft model. In mice, MDSCs coexpress CD11b and myeloid differentiation antigen Gr-1. Gr-1CD11b cells infiltrated allografted corneas between 4 d and 4 wk after surgery; however, the frequencies of Gr-1CD11b cells were not different between accepted and rejected allografts or in peripheral blood or BM. Of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…It has been reported that MDSCs are involved in the pathogenesis of corneal allograft rejection ( 25 27 ) and that RAPA prolongs cardiac-allograft survival and alleviates acute kidney injury by inducing MDSC recruitment and strengthening their immunosuppressive activity ( 28 , 29 ). Based on these findings, we investigated whether MDSCs are associated with the RAPA-induced anti-rejection effect in corneal-transplantation models.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that MDSCs are involved in the pathogenesis of corneal allograft rejection ( 25 27 ) and that RAPA prolongs cardiac-allograft survival and alleviates acute kidney injury by inducing MDSC recruitment and strengthening their immunosuppressive activity ( 28 , 29 ). Based on these findings, we investigated whether MDSCs are associated with the RAPA-induced anti-rejection effect in corneal-transplantation models.…”
Section: Resultsmentioning
confidence: 99%
“…However, MDSCs are known to expand after kidney transplantation in humans 9 . Animal studies have shown that adoptive transfer of MDSCs can prolong survival of islets, skin, as well as cardiac allografts 4,5,36‐38 ; but little more is known about the ability of MDSCs to control graft survival. Our group recently showed that anti‐thymocyte globulin affects MDSC expansion and survival, suggesting that common transplant drugs may alter the immunosuppressive capacities of MDSCs 3 .…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs suppress alloreactive T cell responses and have been shown to prolong islet 4 and corneal 5 graft survival. A contribution of MDSCs in tolerance has been suggested in rodent models of cardiac, 6 kidney, 7 and skin 8 transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…5 In transplantation, several studies demonstrated that MDSCs play an essential role in immune tolerance induction in models of kidney, skin, or heart transplantation. 20 There are several possibilities as to how MDSCs prevent allograft rejection. 20 There are several possibilities as to how MDSCs prevent allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][16][17][18][19] Furthermore, a recent study showed that infiltration of Gr-1 int CD11b + MDSCs in corneal grafts during the early postoperative days led to acceptance of corneal allografts. 20 There are several possibilities as to how MDSCs prevent allograft rejection. One is that MDSCs suppress T cells through iNOS expression and NO production.…”
Section: Discussionmentioning
confidence: 99%